An intrinsic epigenetic barrier for functional axon regeneration - Weng, Yi-Lan (Neuron, 2017)
Mature neurons in the adult peripheral nervous system can effectively switch from a dormant state with little axonal growth to robust axon regeneration upon injury. The mechanisms by which injury unlocks mature neurons’ intrinsic axonal growth competence are not well understood. Here we show that peripheral sciatic nerve lesion in adult mice leads to elevated levels of Tet3 and 5- hydroxylmethylcytosine in dorsal root ganglion (DRG) neurons. Functionally, Tet3 is required for robust axon regeneration of DRG neurons and behavioral recovery. Mechanistically, peripheral nerve injury induces DNA demethylation and upregulation of multiple regeneration-associated genes in a Tet3- and thymine DNA glycosylase-dependent fashion in DRG neurons. In addition, Pten deletion-induced axon regeneration of retinal ganglion neurons in the adult central nervous system is attenuated upon Tet1 knockdown. Together, our study suggests an epigenetic barrier that can be removed by active DNA demethylation to permit axon regeneration in the adult mammalian nervous system.